The Beneficial Effect of Cynodon Dactylon Fractions on Ethylene Glycol-Induced Kidney Calculi in Rats - Khajavi Rad, Abolfazl; Hadjzadeh, Mousa-Al-Reza; Rajaei, Ziba; Mohammadian, Nema; Valiollahi, Saleh; Sonei, Mehdi (Urology Journal, 2011)
Purpose: To assess the beneficial effect of different fractions of Cynodon dactylon (C. dactylon) on ethylene glycol-induced kidney calculi in rats. Materials and Methods: Male Wistar rats were randomly divided into control, ethylene glycol, curative, and preventive groups. The control group received tap drinking water for 35 days. Ethylene glycol, curative, and preventive groups received 1% ethylene glycol for induction of calcium oxalate (CaOx) calculus formation. Preventive and curative subjects also received different fractions of C. dactylon extract in drinking water at 12.8 mg/kg, since day 0 and day 14, respectively. After 35 days, the kidneys were removed and examined for histopathological findings and counting the CaOx deposits in 50 microscopic fields. Results: In curative protocol, treatment of rats with C. dactylon N-butanol fraction and N-butanol phase remnant significantly reduced the number of the kidney CaOx deposits compared to ethylene glycol group. In preventive protocol, treatment of rats with C. dactylon ethyl acetate fraction significantly decreased the number of CaOx deposits compared to ethylene glycol group. Conclusion: Fractions of C. dactylon showed a beneficial effect on preventing and eliminating CaOx deposition in the rat kidney. These results provide a scientific rational for preventive and treatment roles of C. dactylon in human kidney stone disease.